Redox injectable gel protects osteoblastic function against oxidative stress and suppresses alveolar bone loss in a rat peri-implantitis model. (1st July 2020) - Ozawa, Ryotaro; Saita, Makiko; Sakaue, Sho; Okada, Ryusaku; Sato, Takenori; Kawamata, Ryota; Sakurai, Takashi; Hamada, Nobushiro; Kimoto, Katsuhiko; Nagasaki, Yukio
ABSTRACT: Dental implant surgery is a routine treatment in clinical dentistry. However, implant surgery is associated with an increased risk of bacterially induced peri-implantitis and the production of reactive oxygen species (ROS), with no established treatment. We recently designed a new redox injectable gel (RIG) containing nitroxide radicals for the treatment of peri-implantitis. Here, we investigated the antioxidative effect of RIG as a preventive therapy for ROS-associated peri-implantitis in a rat model of alveolar bone resorption and in vitro . In each rat, the maxillary first molar tooth was replaced with a screw-type implant, and rats were assigned to one of four groups: an implant alone, an implant with infection, implant with infection and treatment with nRIG (a non-nitroxide radical-containing injectable hydrogel) or RIG. We confirmed the long-term retention of RIG in the peri-implant region and found that RIG significantly protected the alveolar bone volume and decreased lipid peroxidation. In culture, we found that RIG restored osteoblast proliferation and differentiation in the presence of hydrogen peroxide (H2 O2 )-induced oxidative stress. Moreover, using a malondialdehyde assay of lipid peroxidation, we found that RIG suppressed oxidative stress in H2 O2 -treated rat osteoblasts. Overall, RIG is anticipated as a prophylactic treatment for peri-implantitis and may help preserve oral function. Statement of Significance 1. Implant surgery is associated with an increased risk of bacterially induced peri-implantitis and the production of reactive oxygen species (ROS). We designed a novel redox injectable gel (RIG) containing nitroxide radicals for the treatment of peri-implantitis. In this study, we investigated the antioxidative effect of RIG as a preventive therapy for ROS-associated peri-implantitis in a rat model and in vitro. 2. We showed that treatment with RIG reduces oxidative damage in a rat peri-implantitis model, protecting against bone resorption and a loss of bone density. We showed that RIG inhibits H2 O2 -mediated decreases in proliferation, osteoblast differentiation, and mineralization, and also against lipid peroxidation in vitro. Our results indicate that RIG has an antioxidative effect of peri-implantitis. Graphical abstract: Image, graphical abstract